Rastin Swap Card (RSC): A Financial Instrument of Rastin Banking - Bidabad, Bijan (International Journal of Islamic Banking and Finance Research, 2019)
Rastin Swap Card is defined in Rastin Banking. This card is issued based on the Swap Contract in Rastin Banking or principle of sovereignty rights of contracts. In Rastin Swap Card there are two periods. In the first period card issuer lends money to the cardholder, and in the second period borrows money from card holder instead. At the first stage card issuer credits a certain amount of money for specific time duration to the card of cardholder and requests the cardholder to deposit the same amount for the same period at the end of the cited time duration (first maturity) in the issuer’s deposit account. Card issuer and cardholder can agree for a combination of amount and duration for which the product of them (amount by the duration) be equal for both operations of lending money by the issuer and depositing by the cardholder.Rastin Swap Card (RSD) has no interest rate and is different from conventional debit and credit cards, but considering the ICT-based systems, RSD is being processed and managed through electronic banking systems. Rastin Swap Card can be issued in both local and foreign currencies. Bank receives a fee by offering Rastin Swap Card service. JEL: E43, E44, E52, E58, E62, E63